Genetics of biotin biosynthesis in Bacillus subtilis. - Pai, C H (1975)
Biotin auxotrophs of Bacillus subtilis were isolated and classified into three groups according to growth requirements, cross-feeding pattern, and biotin precursors excreted into culture supernatant fluids. Mutant genes were mapped by transduction using phage PBS1. All presently identified bio genes were linked to aroG with an order of bio-aroG-argA-leu-1. No linked markers were found to the left of the bio loci.